Carbon, nitrogen and phosphorus contents and their ecological stoichiometric characteristics in leaf litter from the Jianfengling Tropical Montane Rainforest - Yin, Shuxuan (Frontiers in Plant Science, 2024)
Investigating carbon (C), nitrogen (N) and phosphorus (P) contents and ecological stoichiometric characteristics in leaf litter from tropical rainforests is crucial for elucidating nutrient cycling and energy flow in forest ecosystems. In this study, a 60-ha tropical montane rainforest dynamic monitoring plot in Jianfengling, was selected as the research site. Leaf litter was collected monthly throughout 2016, and samples from various plant species were identified, resulting in a total of 107 samples collected and analysed. For the 31 dominant species, the leaf litter had C, N and P contents of 312.71 ± 28.42, 4.95 ± 0.46 and 0.40 ± 0.03 g/kg, respectively. The C:N, C:P and N:P ratios were 63.61 ± 7.50, 790.91 ± 82.30 and 12.49 ± 1.00, respectively, indicating moderate variability. The C, N and P contents exhibited greater variability among the plant groups, indicating significant heterogeneity among the samples. In contrast, the data from the subplots exhibited less variability, highlighting significant homogeneity. Overall, the mean carbon, nitrogen and phosphorus contents in the leaf litter from tropical montane rainforests were lower than those observed at national and global scales. The N:P ratios in leaf litter below 14 indicated that nitrogen limited litter decomposition in Jianfengling.However, no significant correlations were observed between the C, N and P contents and their stoichiometric ratios in leaf litter and those in soil. The above results provide important reference data and scientific basis for the nutrient cycling and energy flow processes, and in the future, we can explore the limiting role and mechanism of nitrogen in the decomposition process of leaf litter.